Slag-based geopolymer concrete incorporating ash: effects on thermal performance. Issue 1 (2nd January 2022) - Oyebisi, Solomon; Ede, Anthony; Olutoge, Festus; Owamah, Hilary; Igba, Tobit
ABSTRACT: The thermal performance (TP) of concrete structures is vital to the evaluation of the fire response.  Thus, this study examined the thermal properties slag-based geopolymer concrete (GPC) incorporating corncob ash (CCA). Corncob was valorised and partially used as a substitution for slag under the ambient curing conditions. Sodium hydroxide (SH) solution and sodium silicate (SS) gel were used as alkaline activators at 12, 14, and 16 M concentrations. The TP of GPC was compared with that of Portland cement concrete (PCC). Thermal predictions were developed based on the thermal properties. Based on the findings, GPC exhibited lower thermal conductivity (TC) and thermal diffusivity (TD) with increasing specific heat capacity (SHC), indicating good thermal insulation properties (TIP) compared with PCC. The TIP increased with increasing CCA content in the mixture at all levels of alkaline activators. Thus, CCA improves the insulating capacity of the GPC. In addition, a good correlation exists between the GPC produced and thermal properties. These findings can be beneficial in the hot climate regions and utilised for structural insulating construction concrete. Finally, the proposed models can be used in the assessment of GPC structures incorporating supplementary cementitious materials (SCMs) to enhance the TIP of construction materials.